An Early Exposure of Over-the-Counter Medicine Basic Knowledge among Elementary School Students: Over-the-Counter, knowledge, students - Hanindita, Fizkha; Kencana, Nyoman Bayu Wisnu; Flavia Domitilla Erika Setyajati; Setiawati, Agustina (International Journal of Community Service Learning, 2023)
Recently, self-medication using over-the-counter medicine (OTC) or non-prescription medicine became rapidly popular. Enhancing society's awareness of OTC knowledge and its rational use is greatly significant to promote public health both in adults and children. In the US, a high number of young children are brought to the emergency room due to accidental unsupervised medication each year. Therefore, learning how to self-medicate using OTC at an early age is very critical to improve medication safety in society. This study aims to trained elementary school grades V and IV at the age of 10 to 12 to perceive the basic knowledge of OTC and how to take them safely. This study conducted outreach to students in grades V and VI starting with a pre-test, education dan training, followed by a question-and-answer session, and closed with a post-test. After education and training, the knowledge of the OTC among the students increased, especially significantly in Grade V indicated by post-test score elevating. Thus, this attempt may contribute to increasing the awareness of self-medication using OTC among children.